(untitled) (Journal of Engineering, 2024)
As a result of the rising amount of ceramic waste generated by demolition operations and the breaking down of ceramic products during transmission and production processes, the need to get rid of this waste increased. In addition to the importance of preserving natural resources, the trend has begun to utilize these wastes as a partial alternative to aggregates. In this research, it was studied to replace (30%) of the volume of coarse aggregate with crushed ceramic, replacing 10% by weight of cement with local metakaolin and Carbon fibers were added with (1%) by weight of the cementitious material in order to produce pervious concrete in terms of sustainability. Compressive strength, splitting, and density tests were performed. The results showed that the density of the mixture containing (30%) crushed ceramic decreased by (19.4 %) compared to the reference mixture. As for the results of the mixture containing (30%) crushed ceramic, (10%) metakaolin, and (1%) carbon fiber, it decreased compressive strength by (4.14%) and increased in splitting by (29.95 %) compared with the reference mixture at 28 days.